Relationships between surface and underwater swimming with force-velocity profile - Gonzalez Frutos, P.; Guimard, A.; de la Fuente, B.; Segovia, C.; Veiga, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The force-velocity profile (FVP) has shown a relationship with swimming performance (1). However, only 38% of French trainers evaluate strength and speed parameters for some exercises, possibly due to accessibility problems (especially due to price) to modern evaluation devices (2). Recent research has shown a relationship with sprint performance of the Bosco FVP, which is a simplified method that is easy to access and perform (3). Therefore, the objective of the study is to analyze the relationship of Boscos FVP with swimming performance, specifically surface and underwat METHODS: Seventeen junior swimmers performed both swimming and jumping tests. Swimming test consists of six 25 m maximal sprints from a push start in surface (front-crawl) and underwater (undulatory) conditions with three minutes rest between repetitions and conditions (in random order). Jumping test consists of CMJ and a CMJ50 (CMJ with external loads equivalent to 50% of the swimmers´ bodyweight). The best of three attemps was selected for each jump. FVP50 was calculated using Bosco´s Index (FVP50 = CMJ50/CMJ*100). RESULTS: Underwater condition showed higher mean 25 m times (16.96 ± 0.74 s vs 14.00 ± 0.86 s; p < 0.05) and fatigue index (4.50 ± 2.25 % vs 1.92 ± 0.90 %; p < 0.05). Surface swimming mean 25 m times showed very large (r = - 0.73, p < 0.05) and large (r = - 0.63, p < 0.05) relationship with CMJ (32.55 ± 5.04 cm) and CMJ50 (16.81 ± 3.12 cm) performance, respectively. Whereas underwater mean 25 m times only showed large (r = - 0.51, p < 0.05) relationship with CMJ performance. However, Bosco´s FVP50 (51.41 ± 3.64 %) only showed large relationship (r = -0.58; p < 0.05) with underwater swimming fatigue index. CONCLUSION: This study highlighted that underwater swimming may require higher explosive strength (CMJ) to improve mean 25 m times, but higher Bosco´s FVP50 (strength profile) to improve fatigue index, as has been observed in field hockey players (3). However, surface swimming may require higher CMJ and CMJ50 to improve mean 25 m times, not finding a relationship with the fatigue index because swimmers in this condition maintained better performance (possibly related to the free breathing).